Low rate of interchromosomal rearrangements during old radiation of gekkotan lizards (Squamata: Gekkota) - Johnson Pokorná, Martina; Trifonov, Vladimir A; Rens, Willem; Ferguson-Smith, Malcolm A; Kratochvíl, Lukáš (Chromosome research, 2015)
Gekkotan lizards are a highly specious (∼1600 described species) clade of squamate lizards with nearly cosmopolitan distribution in warmer areas. The clade is primarily nocturnal and forms an ecologically dominant part of the world nocturnal herpetofauna. However, molecular cytogenetic methods to study the evolution of karyotypes have not been widely applied in geckos. Our aim here was to uncover the extent of chromosomal rearrangements across the whole group Gekkota and to search for putative synapomorphies supporting the newly proposed phylogenetic relationships within this clade. We applied cross-species chromosome painting with the recently derived whole-chromosomal probes from the gekkonid species Gekko japonicus to members of the major gekkotan lineages. We included members of the families Diplodactylidae, Carphodactylidae, Pygopodidae, Eublepharidae, Phyllodactylidae and Gekkonidae. Our study demonstrates relatively high chromosome conservatism across the ancient group of gekkotan lizards. We documented that many changes in chromosomal shape across geckos can be attributed to intrachromosomal rearrangements. The documented rearrangements are not totally in agreement with the recently newly erected family Phyllodactylidae. The results also pointed to homoplasy, particularly in the reuse of chromosome breakpoints, in the evolution of gecko karyotypes.
Keywords: Animals; malování chromozomů; Chromosome Painting; Evolution, Molecular; karyotyp; molekulární evoluce; metafáze; Metaphase; Phylogeny; Recombination, Genetic; Chromosomes; Karyotype; Lizards; hybridizace in situ fluorescenční; ještěři; zvířata; translokace genetická; In Situ Hybridization, Fluorescence; fylogeneze; chromozomy; rekombinace genetická; Translocation, Genetic